A PHILOLOGICAL STUDY AND ANALYSIS OF TAFSIR METHODOLOGY: The 19th-Century Palembang Malay Qur’an Commentary Manuscript by Masagus Muzammil - Kuswandi, Dedi; Rusli, Ris'an; Umi Kalsum, Nyimas (TAJDID: Jurnal Ilmu Ushuluddin, 2025)
This study examines the manuscript of the Malay Palembang Tafsir written by Masagus Muzammil using a philological approach. This study focuses on two aspects: the philological aspects present in the manuscript and the analysis of the tafsir methodology employed. The research method applied is qualitative with a descriptive-analytical type, focusing on the Al-Qur'an manuscript" atau " using the Al-Qur'an manuscript as the primary source. Data collection techniques include literature studies, direct observation of the manuscript’s physical and textual features, interviews with relevant sources (including descendants of the author), and documentation of manuscript conditions. The results indicate that the Malay Palembang Tafsir manuscript is written on European paper, which has its own distinctive characteristics. The tafsir is organized systematically according to the order of the mushaf, presented concisely, and employs non-conventional academic formatting. Furthermore, the references used are derived from previous tafsir texts, reflecting the existing tradition of interpretation. The findings reveal that the Malay Palembang Tafsir manuscript (c. 1860 CE), written on European paper with watermarks, is arranged according to the mushaf order and presented in a global, non-academic format. It applies a Sufi and socio-community interpretive style, using the tafsir bi al-ra’yi method, with both textual and contextual approaches. Academically, this study exposes the methodological hybridity of Malay tafsir traditions and shows how the manuscript bridges classical Islamic scholarship with Southeast Asian hermeneutics, highlighting the adaptive and dynamic nature of 19th-century Malay-Islamic intellectual thought.